Hospital incidence, mortality, and gender disparities in patients treated for type A aortic dissections in Switzerland – a secondary data analysis of Swiss DRG statistics (Swiss Medical Weekly, 2023)
AIMS OF THE STUDY: The incidence of type A aortic dissection (TAAD) has increased in several countries in recent decades, but epidemiological data for Switzerland are lacking. Furthermore, there are conflicting data regarding a gender-disparity with higher type A aortic dissection mortality in women. This study analysed sex-specific hospital incidence and in-hospital mortality rates of TAAD in Switzerland.METHODS: This study is a secondary data analysis of case-related hospital discharge data from the Swiss Federal Statistical Office for 2009–2018. Cases that were hospitalised and surgically treated for type A aortic dissection were included in this analysis. Standardised incidence rates were calculated using the European standard population in 2013. All-cause in-hospital mortality rates were calculated as raw values and standardised for age, sex, and the van Walraven comorbidity score.RESULTS: A total of 2117 participants were included in this study, of whom 67.1% were male. The age-standardised cumulative hospital incidence for type A aortic dissection treatment was 3.5 per 100,000 (95% CI: 3.3–3.7) for men and 1.7 (1.6–1.8) per 100,000 for women (p